x + 18 = 2y; y = 2x – 9

(v) x + 18 = 2y; y = 2x – 9



Sol. x + 18 = 2y

 x – 2y = – 18

y = 2x – 9

 – 2x + y = – 9

Changing the sign,

2x – y = 9


D
=
1
-2
=
(1 × -1) – (2 × -2)
=
-1 + 4
=
3


2
-1







DX
=
-18
-2
=
(-18 × -1) – (9 × -2)
=
18 + 18
=
36


9
-1









DY
=
1
-18
=
(1 × 9) – (2 × -18)
=
9 + 36
=
45


2
9









By Cramer's rule,

x
=
Dx
=
36
=
12


D

3





y
=
Dy
=
45
=
15


D

3





x = 12 and y = 15 is the solution of given simultaneous equations.

No comments:

Post a Comment